Implementation of Innovative Learning for Teacher Professional Education in the Eastern Region of Indonesia - Poluakan, Cosmas; Silangen, Patricia; Ratulangi, Norita; Utari, Kadek Si (International Journal of Information Technology and Education, 2024)
Innovative learning in the 21st century requires students to have the ability to think critically, creatively, and communicatively and be able to collaborate. For this purpose, research has been carried out on Professional Teacher Education (PPG) students at Manado State University. The research aims to implement the Problem-Based Learning (PBL) and Project Based Learning (PjBL) learning models through Field Experience Program (PPL) activities. The study was conducted on a sample of 36 elementary school teachers with a total sample of 252 students in the Eastern Region of Indonesia, including the provinces of Papua, Maluku, East Nusa Tenggara, West Nusa Tenggara, Central Sulawesi, Southeast Sulawesi and North Sulawesi. Experimental research method with the application of the PBL and PjBL models. Data was obtained from online workshop interviews and the Learning Management System (LMS) owned by the Directorate of Teacher Professional Education, Directorate General of Teachers and Education Personnel of the Republic of Indonesia. The data is processed from the Learning Implementation Plan (RPP) documents and Teaching Modules created by the teacher then reviewing the Teaching Materials, Student Worksheets, Assessment Instruments, and Learning Media. Student learning outcomes are taken from the pre-test and post-test formative scores. The results of the data analysis showed that there was a significant increase in learning outcomes from an average Pre-Test score of 52.2 and after the learning process, the average Post-Test score increased to 84.5. This happened because the PBL and PjBL learning models had been implemented which reached 98.8%. The above learning outcomes occurred because innovative learning elements were implemented, namely 87.7% of learning based on Higher Ordered Thinking Skills, 80% of learning using Group Worksheets, 20% using Individual Worksheets, 67% of learning using Technological Pedagogical Content Knowledge (TPACK) 33% of lessons use TPACK accompanied by Student Books and Teaching Aids. Based on the research results above, the use of PBL and PjBL in learning is a necessity. The PBL and PjBL learning models trigger and encourage students to become more creative in learning by prioritizing collaborative learning and being able to communicate experiences and learning results obtained through analytical and critical thinking.